Storytelling Sebagai Metode Dakwah Pada Anak Usia Dini (Analisis Chanel Youtube Anak Muslim) - Luthfi Hidayah; Iga Nur Rohmatillah (El-Fatih: Jurnal Dakwah dan Penyuluhan Islam, 2024)
This research aims to determine storytelling as a method of da'wah in early childhood (Analysis of YouTube Channels for Muslim Children). The type of research used is a case study approach. The research methodology that the author uses is qualitative, namely interpretive research (field research) which uses inductive reasoning methods and focuses on social phenomena. In analyzing research problems, the author focuses on using Uses and Gratification Theory, where researchers have the freedom to be more active in choosing YouTube content to be researched. This research uses data collection methods in the form of observation and documentation. The research subjects that the author studied were early childhood children starting from PAUD, Kindergarten A and Kindergarten B. Children aged 1-6 years. The results of this research include that da'wah through the storytelling method allows children to develop good language creativity, both formal and non-formal, then it can stimulate children to like reading and hopefully can shape children's character from an early age. so that it can increase imagination, communication and interaction. in children.